2016
DOI: 10.1002/mc.22479
|View full text |Cite
|
Sign up to set email alerts
|

Functional activation of PPARγ in human upper aerodigestive cancer cell lines

Abstract: Upper aerodigestive cancer is an aggressive malignancy with relatively stagnant long-term survival rates over 20 yr. Recent studies have demonstrated that exploitation of PPARγ pathways may be a novel therapy for cancer and its prevention. We tested whether PPARγ is expressed and inducible in aerodigestive carcinoma cells and whether it is present in human upper aerodigestive tumors. Human oral cancer CA-9-22 and NA cell lines were treated with the PPAR activators eicosatetraynoic acid (ETYA), 15-deoxy-δ-12,14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…To our knowledge, this is the first epidemiological study using population‐based case‐control methodology to assess the association between pioglitazone use among patients with type 2 DM and the subsequent occurrence of HNC. Our findings contradict previous laboratory research findings, two phase II clinical trials, and a prospective cohort study, which suggested a chemoprotective effect of pioglitazone in oral/head and neck cancers. Notably our study not only showed no protective effect but, on the contrary, shows increased odds of oral cavity and HNC cancer with pioglitazone use.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, this is the first epidemiological study using population‐based case‐control methodology to assess the association between pioglitazone use among patients with type 2 DM and the subsequent occurrence of HNC. Our findings contradict previous laboratory research findings, two phase II clinical trials, and a prospective cohort study, which suggested a chemoprotective effect of pioglitazone in oral/head and neck cancers. Notably our study not only showed no protective effect but, on the contrary, shows increased odds of oral cavity and HNC cancer with pioglitazone use.…”
Section: Discussioncontrasting
confidence: 94%
“…PPARγ agonists as a chemoprevention agent for HNC have been established in many laboratory studies . There remains a paucity of human clinical studies, specifically whether PPARγ agonists such as pioglitazone used in patients with type 2 DM could be preventive against HNC .…”
Section: Introductionmentioning
confidence: 99%
“…PPARg, a member of the nuclear receptor family, has been detected both in humans and mice. It acts as one of the key factors regulating glucose metabolism and involves in pathologies of various diseases such as obesity, cancer, and inflammation (46,47). C/EBPa, a member of the basic region leucine zipper family of transcription factors, is involved in adipogenesis of the liver and adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of PPARγ activation on lung cancer cells is associated with decreased expression of anti‐apoptotic regulators Bcl‐2 and Bcl‐w, and activation of extracellular signal regulated kinase (ERK) and p38 mitogen activated protein kinase (p38MAPK) (Giaginis et al, ). PPARγ ligand binding is known to induce PPARγ expression and inhibit proliferation in human oral cancer cells (Wright et al, ). In gastric cancer cells, PPARγ signaling induces tumor growth, and the PPARγ ligand, troglitazone, induces apoptosis via an increase in the level of pro‐apoptotic proteins Bax/Bcl‐2 (Fukuoka et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…protein kinase (p38MAPK) (Giaginis et al, 2012). PPARγ ligand binding is known to induce PPARγ expression and inhibit proliferation in human oral cancer cells (Wright et al, 2017). In gastric cancer cells, PPARγ signaling induces tumor growth, and the PPARγ ligand, troglitazone, induces apoptosis via an increase in the level of proapoptotic proteins Bax/Bcl-2 (Fukuoka et al, 2015;Liu et al, 2013).…”
mentioning
confidence: 99%